2015
DOI: 10.1016/j.jvs.2015.01.051
|View full text |Cite
|
Sign up to set email alerts
|

Association of dual-antiplatelet therapy with reduced major adverse cardiovascular events in patients with symptomatic peripheral arterial disease

Abstract: DAPT may be associated with reduced rates of MACEs and death among patients with symptomatic peripheral arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 45 publications
0
55
1
Order By: Relevance
“…We chose to study only Aspirin as our mono-antiplatelet group as it makes this study more readily comparable to CHARISMA and to Armstrong et al, and is the most common antiplatelet agent used in patients with PAD. [20, 21]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to study only Aspirin as our mono-antiplatelet group as it makes this study more readily comparable to CHARISMA and to Armstrong et al, and is the most common antiplatelet agent used in patients with PAD. [20, 21]…”
Section: Methodsmentioning
confidence: 99%
“…An early single-center observational study in a PAD population showed a reduction in MACE and mortality associated with DAPT, and subgroup analysis from the CHARISMA trial, showed a similar reduction in MI associated with DAPT, suggesting this might be true. [20, 21]…”
Section: Introductionmentioning
confidence: 99%
“…After a median follow-up period of over 2 years, the primary composite endpoint of MI, stroke, or death from cardiovascular causes did not differ significantly among treatment groups in the overall cohort (6.8 % in the DAPT group vs 7.3 % in the aspirin monotherapy group; HR 0.93; 95 % CI 0.83-1.05; p = 0.22) or in the subgroup of 3096 patients with PAD (7.6 % in the DAPT group vs 8.9 % in the aspirin monotherapy group; HR 0.85; 95 % CI 0.66-1.08; p = 0.18) [44]. A recent observational cohort analysis of 629 patients with symptomatic PAD undergoing diagnostic or interventional lower extremity angiography demonstrated lower rates of MACE (HR 0.65; 95 % CI 0.44-0.96) and overall mortality (HR 0.55; 95 % CI 0.35-0.89) in patients treated with DAPT compared to aspirin alone, suggesting that longer-term DAPT may improve outcomes in patients with PAD undergoing endovascular interventions [45].…”
Section: Antithrombotic Therapymentioning
confidence: 99%
“…Data regarding the optimal duration of antiplatelet therapy following endovascular intervention is limited. Most patients are treated with indefinite aspirin therapy and 1 to 3 months of clopidogrel, a practice extrapolated from data for PCI, though observational data suggests that longerterm DAPT may improve outcomes in patients with PAD undergoing endovascular interventions [45]. Finally, vorapaxar has been shown to reduce acute limb ischemia and need for revascularization in patients with PAD, including those with recent surgical and endovascular revascularization, with an attendant risk of bleeding [46•, 82].…”
Section: Antithrombotic Therapy Following Revascularizationmentioning
confidence: 99%
“…The relatively lower rate of statin and P2Y12 inhibitor utilization is a crucial shortcoming in the optimization of medical therapy in these patients given the known protective role for limb. 15,16 Third, the authors meticulously examined the potential interaction between frailty and 3 clinical factors: age ≤75 or >75 years old, endovascular versus surgical revascularization, and renal function status. Additional analyses on the other baseline characteristics that significantly differed based on the frailty score (ie, body mass index, dyslipidemia, diabetes mellitus, smoking status, Rutherford classification, and tissue loss) would have been instructive.…”
mentioning
confidence: 99%